This is true because 2/5 = 4/10
If u gave 1/10 of a pizza to 6 friends then you would have given them 6/10 of your pizza and have 4/10 left over because 4/10 + 6/10 = 10/10 or 1
Hope this helped :)
Answer:
lolllll
Step-by-step explanation:
Let the width be x.
Then,Length = ( 2x - 3 ) m
<u>According to the question, </u>
Area of rectangle = 665 m² [ Given ]
Formula: Area of rectangle = Length × Width
![\sf \implies \: length \: \times breadth = 665 \: m {}^{2}](https://tex.z-dn.net/?f=%20%5Csf%20%5Cimplies%20%5C%3A%20length%20%5C%3A%20%20%5Ctimes%20breadth%20%3D%20665%20%5C%3A%20m%20%7B%7D%5E%7B2%7D%20)
![\sf\implies \: (2x - 3) \times x = 665](https://tex.z-dn.net/?f=%20%20%5Csf%5Cimplies%20%5C%3A%20%282x%20-%203%29%20%5Ctimes%20x%20%3D%20665)
![\sf \implies \: 2 {x}^{2} - 3x = 665](https://tex.z-dn.net/?f=%20%5Csf%20%5Cimplies%20%5C%3A%202%20%7Bx%7D%5E%7B2%7D%20%20-%203x%20%3D%20665)
![\sf \implies \: {2x}^{2} - 3x - 665 = 0](https://tex.z-dn.net/?f=%20%5Csf%20%5Cimplies%20%5C%3A%20%20%7B2x%7D%5E%7B2%7D%20%20-%203x%20-%20665%20%3D%200)
<u>By split middle term </u>
![\sf \implies \: 2 {x}^{2} - 38x + 35x - 665 = 0](https://tex.z-dn.net/?f=%20%5Csf%20%5Cimplies%20%5C%3A%202%20%7Bx%7D%5E%7B2%7D%20%20-%2038x%20%20%2B%2035x%20-%20665%20%3D%200)
![\sf\implies \: 2x(x - 19) + 35(x - 19) = 0](https://tex.z-dn.net/?f=%20%20%5Csf%5Cimplies%20%5C%3A%202x%28x%20-%2019%29%20%2B%2035%28x%20-%2019%29%20%3D%200)
![\sf \implies \: (2x + 35) = 0 \: or \: (x - 19) = 0](https://tex.z-dn.net/?f=%20%5Csf%20%5Cimplies%20%5C%3A%20%282x%20%2B%2035%29%20%3D%200%20%5C%3A%20or%20%5C%3A%20%28x%20%20-%2019%29%20%3D%200)
![\sf \implies \: x = \dfrac{ - 35}{2} \: or \: \: x = 19 \:](https://tex.z-dn.net/?f=%20%5Csf%20%5Cimplies%20%5C%3A%20x%20%3D%20%20%5Cdfrac%7B%20-%2035%7D%7B2%7D%20%20%5C%3A%20or%20%5C%3A%20%20%5C%3A%20x%20%3D%2019%20%5C%3A%20)
Note: Ignore negative number.
Now,
Width of a rectangle = 19 m
Length of a rectangle = 2x - 3 = 2 × 19 - 3 = 38 - 3 = 35 m
Answer:
=
+
+ C where C is the constant of integration.
Step-by-step explanation:
i)it is given that the rate of change of W with respect to x is proportional to
x + 18. Therefore
= k(x + 18) where k is a constant.
ii) Therefore
=
+
+ C where C is the constant of integration.
iii) the complete solution can only be found if we know the constant of proportion and also the constant of integration.